Autodetection of a Target by Eye Movement. Issue 6 (19th June 2015) - Hareli, Shlomo; Nave, Ophir
Abstract : Locating an unknown object position in a map by information stored in the unconscious mind is important from practical point of view. Locating captives, bomb, or terrorist secret bases by interrogation is problem that the intelligent agencies face daily. The person interrogated may have the desired information stored in unconscious or may not know it at all. In this article, we will present a novel way of retrieving the object location based on eye movement. The technique is based on a Bayesian mathematical approach to localization, in which measured count rates of eye fixation and duration, the probability of the location of the target is correlated with the count rate and drops as the distance increases from the fixation location. We focused on the discrete model and then generalized it to continuous model. © 2015 Wiley Periodicals, Inc. Complexity 21: 452–459, 2016